Seasonal variation of nutrient content in the foliage of Jatropha curcas - Silva de Lima, Rosiane de Lourdes; Vieira de Azevedo, Carlos Alberto; Gheyi, Hans Raj; Sofiatti, Valdinei; Cazetta, Jairo Osvaldo; Carvalho Junior, Genelicio Souza [UNESP]; Castro Arriel, Nair Helena (Univ Estadual Londrina, 2014)
Physic nut (Jatropha curcas) is a perennial crop cultivated for the production of oil. Achieving high productivity depends on a profound knowledge of nutritional demand and the appropriate time for fertilization. This study aimed to register the seasonal variation of content of nutrients in leaf and to determine the most suitable time for performing analysis of leaf. For the study, treatments were defined as a factorial combination of 10 months (February, March, April, May, June, August, September, October, November and December) and two provenances of leaf tissues (tissues originating from vegetative branches and coming from fruiting terminals). A completely randomized design was used with four replications and two plants were sampled each time. Foliar concentrations of N, P, K, Ca, Mg, S, Cu, Fe, Mn and Zn showed a wide variation between leaf shedding period through bloom and fruit filling, but the variation was narrow in the period before the leaf shedding phase or the phase of physiological rest. Therefore, the most appropriate time to assess the nutritional status of plants of Jatropha is at the end of the reproductive period during the 30 days preceeding leaf shedding.
Variação sazonal dos teores de nutrientes nas folhas de pinhão-manso
Keywords: Sampling time; mineral nutrition; oilseed crop; Jatropha curcas